2019
DOI: 10.3390/inorganics7010010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Theranostic Agents for Photodynamic Therapy (PDT) and Magnetic Resonance Imaging (MRI)

Abstract: Magnetic resonance imaging (MRI) is a powerful non-invasive diagnostic tool that can provide important insights for medical treatment monitoring and optimization. Photodynamic therapy (PDT), a minimally invasive treatment for various types of tumors, is drawing increasing interest thanks to its temporal and spatial selectivity. The combination of MRI and PDT offers real-time monitoring of treatment and can give significant information for drug-uptake and light-delivery parameters optimization. In this review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Further imaging techniques make use of specific paramagnetic or radiolabeled metalloporphyrins as contrast agents for magnetic resonance imaging (MRI) [ 35 , 36 ], and positron emission tomography (PET) [ 37 , 38 ] or near-infrared (NIR)-absorbing porphyrins for photoacoustic imaging (PAI) [ 39 , 40 ] of tissue. Concomitant with the development of multimodal drugs, more recently, porphyrins are investigated as potential theranostics combining therapeutic and diagnostic functions [ 19 , 41 , 42 ]. Finally, the application of porphyrinic compounds in drug delivery should be mentioned in connection with the design of smart, stimuli-responsive platforms for controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…Further imaging techniques make use of specific paramagnetic or radiolabeled metalloporphyrins as contrast agents for magnetic resonance imaging (MRI) [ 35 , 36 ], and positron emission tomography (PET) [ 37 , 38 ] or near-infrared (NIR)-absorbing porphyrins for photoacoustic imaging (PAI) [ 39 , 40 ] of tissue. Concomitant with the development of multimodal drugs, more recently, porphyrins are investigated as potential theranostics combining therapeutic and diagnostic functions [ 19 , 41 , 42 ]. Finally, the application of porphyrinic compounds in drug delivery should be mentioned in connection with the design of smart, stimuli-responsive platforms for controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement in medicine, drug designing has revolutionized from the utilization of different drugs for therapy and diagnostics separately to theranostics by integration of therapeutic and diagnostics potential into a single drug molecule 31 . In 1998, Funkhouser coined the term “Theranostic” defining those materials that combine both therapeutic approach and diagnostic imaging in a single entity, so that both the agents are delivered at the same time will show the same biodistribution pattern 31 , 32 . The theranostic field has the advantage of tuning the therapy and dose by gaining the ability to image and monitor the diseased tissue, delivery kinetics, and drug efficacy.…”
Section: Theranostics: ''Multifunctional Agents'' For Image-guided Photodynamic Therapymentioning
confidence: 99%
“…Further, studies have shown that PDT-induced changes alter proton behaviors in the tumor tissue and such changes can be enhanced using MRI contrast agents. Thus, MRI-guided PDT allows the determination of treatment parameters like PS concentration, light dose in relation to the final treatment outcome 32 .…”
Section: Theranostics: ''Multifunctional Agents'' For Image-guided Photodynamic Therapymentioning
confidence: 99%
See 2 more Smart Citations